Estudo dos aspectos reprodutivos em Luehea divaricata Martius (Açoita-cavalo) - Grave, Fernanda (2005)
The Luehea divaricata Martius (açoita-cavalo) is a tree of Tiliaceae family that is of the interest of industries due to wood the quality and also reflorestation programs. Studies about propagation are justified mainly when working with native plants, that have few research results. Two studies were conducted about specie propagation: one vegetative way and another by sexual way. The first study tried to determinate the collection period of cuttings and concentration of AIB fitorregulator ideals employed in the vegetative propagation of Luehea divaricata. Cuttings with 10cm received asseptical treatment and stayed for seven days in the environment of rooting induction 1/4 WPM + concentration (T1); 0,1 (T2); 1,0 (T3); 10,0 mg/L (T4) of AIB, as applied treatment in the collected cuttings in these following periods of cuttings: nov/2003, fev/2004, may/2004, aug/2004. After this period, they were transfered for the environment formation of roots (1/4 WPM). On the 60th day were analyzed the variables dry mass of roots (g), average root lenght (cm), roots numbers, and also diameter aspects of stem (cm) and dry mass of the aero part (g). In the second study, it was verified the better substract and which improves more the growth of seedlings come from seeds. Four substracts were tested: Plantmax®, turfa, carbonizated crust rize, and Mec Plant®. At 60, 120 and 180 days after the sowing, the development was evaluated of seedlings from the variables: root dry mass (g), stem diameter (cm), aero part fresh mass (g), aero part dry mass (g), aero part height (cm) and the total of leaves. In the propagation of specie by cutting, in all collection periods, excepted aug/2004, until the concentration of 5 mg/L of AIB, there wan an increase of vigor, of uniformity and quality of the root system. The collection of feb/2004 got the best results for the analyzed parameters. In the sexual propagation, the seed germination of Luehea divaricata occurred in all the tested substracts. In the Plantmax® commercial substract on the 180th day after the sowing (Third and last avaliation) in the roots dry mass parameters, fresh and dry mass the aero part results four times better, were achieved. In all variables analyzed, the results of four times more hight at 180 days, Plantmax® got a superior development comparing to the other substracts.